Non-reperfused Inferior Wall Myocardial Infarction with Total Atrioventricular Block - Patricia Feliani Sitohang (Cermin Dunia Kedokteran, 2019)
Inferior wall myocadial infarction (IWMI) with total atrioventricular block (TAVB) is associated with poor clinical status, such as right ventricular infarction (RVI). In IWMI patients with RVI and TAVB, coronary reperfusion using primary percutaneous coronary intervention (PCI) or fibrinolysis can preserve ventricular function and reduce mortality and morbidity. Bradyarrhythmia with hypotension and TAVB is one of the main indications to temporary pacing. This is a case of infero-posterior wall myocardial infarction, RVI, with TAVB. Primary PCI or fibrinolysis and temporary pacing was suggested, but the patient refused. Treatments were atropine sulfate and dopamine for bradycardia and hypotension. Dual-antiplatelet with aspirin and clopidogrel along with fondaparinux was given for antithrombotic therapy. The ECG showed resolution of STEMI and improvement in heart rhythm after 48h. Infark miokardial dinding inferior dengan blok atrioventrikular total dikaitkan dengan status klinis buruk, seperti infark ventrikel kanan. Pada pasien infark miokardial dinding inferior dengan infark ventrikel kanan dan blok atrioventrikular total, reperfusi koroner dengan intervensi koroner perkutan primer atau fibrinolisis dapat melindungi fungsi ventrikel dan mengurangi mortalitas serta morbiditas. Bradiaritmia dengan hipotensi dan blok atrioventrikular total adalah salah satu prioritas utama pemasangan pacu jantung sementara. Kasus ini membahas pasien pria dengan infark miokard infero-posterior, infark ventrikel kanan, dengan blok atrioventrikular total. Pasien menolak intervensi koroner perkutan primer atau fibrinolisis serta pacu jantung sementara. Terapi atropin sulfat dan dopamin untuk bradikardia dan hipotensi; terapi antitrombotik berupa dual-antiplatelet dengan aspirin dan clopidogrel bersama fondaparinux. EKG menunjukkan resolusi STEMI dan perbaikan irama jantung setelah 48 jam. Pada pasien non-reperfusi, diperlukan antitrombotik yang tepat.